Management of adverse events induced by next-generation immunomodulatory drug and proteasome inhibitors in multiple myeloma. Issue 1 (2nd January 2017) - Salvini, Marco; Bonello, Francesca; Boccadoro, Mario; Larocca, Alessandra
ABSTRACT: Introduction : In the last decade the introduction of novel agents has strongly improved multiple myeloma prognosis by doubling median overall survival. Unfortunately disease relapse is very common and patients may become refractory to previous drugs. Therefore, new therapeutic strategies are urgently needed. Areas covered : We have reviewed the available data on next generation novel agents, particularly immunomodulatory drug pomalidomide and proteasome inhibitors carfilzomib and ixazomib, the latter being the first-in-class orally available. We focused on adverse events associated with such agents and described how they should be managed. The main grade ≥3 adverse events correlated with these drugs are hematologic, myelosuppression-related and reversible; non-hematologic grade ≥3 toxicities are less frequent, with an incidence of <10%. Expert commentary : These agents showed to have a good tolerability. The great majority of adverse events are easily manageable with dose-adjustment and appropriate treatment, and drug discontinuation is not frequent. Favorable safety profile and high efficacy, especially in combination, confer to these drugs a central role in development of new lines of therapy against multiple myeloma. Further investigation is certainly needed to determine the best combinations including these agents.